Factors influencing refugees' willingness to accept COVID‐19 vaccines in Greater Sydney: a qualitative study. (12th May 2022) - Mahimbo, Abela; Kang, Melissa; Sestakova, Lidija; Smith, Mitchell; Dawson, Angela
Abstract: Objectives : Achieving high vaccination coverage is a critical strategy to reducing the spread of COVID‐19 infection. This study, undertaken before the Delta variant outbreak, aimed to understand potential drivers and barriers influencing COVID‐19 vaccine uptake for refugees. Methods : Four focus group interviews were conducted with 37 refugees from four language groups (Arabic, Dari, Dinka and Karen). Data were analysed thematically. Results : Willingness to accept COVID‐19 vaccines was associated with participants' perceptions of disease severity, and benefits such as increased immunity against COVID‐19 disease and prevention of the spread of the disease. Cues for increasing individual willingness to get vaccinated included obtaining information from trusted sources and community engagement. By contrast, information gaps on vaccines compounded by misinformation on social media contributed to a reluctance to be vaccinated. Conclusion : As this study was conducted before the Delta variant outbreak, participants' stance on COVID‐19 vaccines may have changed. However, addressing vaccine literacy needs for this group remains an on‐going priority. Health promotion initiatives must be tailored to the different socio‐cultural contexts of each community. Implications for public health : Engagement with refugee populations is critical for optimising access and uptake of vaccines to protect health, prevent death and ensure that control of the pandemic is equitable. This may also provide valuable public health lessons for other marginalised populations.